University key performance indicator management model (e-KPIus) / Mohd Azry Abdul Malik ...[et al.] - Abdul Malik, Mohd Azry; Mustapha, Muhammad Firdaus; Mohamad, Roslim; Md Noor, Mohd Rahimie; Ismail, Zurina (2020)
Coordinating numerous projects conducted by various parties within the university is a daunting task as it involves many individuals and groups. To make it easier for Strategic Planning Unit (UPS) of UiTM Cawangan Kelantan to monitor all projects being worked on, an application named the Key Performance Indicator Management Model (e-KPIus) was developed. The „e-KPIus‟ is a systematic approach to data collection, and supervision of the project progress by the top management and serves as an information sharing platform. eKPIus gives significant and valuable contributions to UPS as it ensures the quality control and improvement in the context of UPS data management. Although the idea of the application developed is undoubtedly convincing, the effectiveness of the application is yet to proof. Thus, a study was undertaken aiming at assessing the effectiveness of e-KPIus. A total of 40 respondents consist of project executors, and performance indicators (PI) keepers at UiTM Cawangan Kelantan participated in this study. Findings revealed that e-KPIus has received a favorable response from users. This project suggested that the e-KPIus can be used to enhance the quality of data management process in UPS and has a great potential to be extended to other departments to ensure better quality of performance management